Struma ovarii with contralateral ovarian teratoma: A case report - Bai, Jiao; Ren, Xinjie; Guo, Zhaoyou (Frontiers in Surgery, 2022)
Struma ovarii (SO) is a rare form of ovarian teratoma in which the thyroid tissue constitutes over 50% of the tumor. SO comprise 1% of all ovarian tumors. We report the case of a 61-year-old woman who was admitted to the hospital because of frequent urination and dysuria. Abdominal magnetic resonance imaging revealed a mass measuring approximately 16 cm in diameter in the right adnexal area. After transabdominal bilateral adnexectomy, pathological examination revealed a teratoma of the ovary on the right and goiter of the ovary with focal thyroid cancer on the left side. Subsequent total thyroidectomy was performed, and no cancer was found on pathological examination. The patient was treated with thyroxine for a long time after the operation, and there was no recurrence 3 years after diagnosis.